Diversity and Geographical Distribution of Sand Flies Phlebotomus papatasi (Diptera: Phlebotominae) by using Geometric Morphometric Technique from two Iraqi Provinces (Baghdad Science Journal, 2020)
The variation in wing morphological features was investigated using geometric morphometric technique of the Sand Fly from two Iraqi provinces Babylon and Diyala . We distributed eleven landmarks on the wings of Sand Fly species. By using the centroid size and shape together, all species were clearly distinguished. It is clear from these results that the wing analysis is an essential method for future geometric morphometry studies to distinguish the species of Sand Flies in Iraq.